Nutritive Value and Nutrient Digestibility of Silages From Different Parts of Fodder Beet With or Without Lactobacillus buchneri Inoculants for Sheep - Ali Abdi Saray; Alireza Aghashahi; Abolfazl Zali; Mehdi Ganj Khanlou; Einar Vargas‐Bello‐Pérez; Navid Ghavipanje (Veterinary Medicine and Science, 2026)
ABSTRACT Objective This study aimed to evaluate the suitability of diets containing silages from different parts of fodder beet (FB) with or without Lactobacillus buchneri (LB) when fed to sheep. Methods Seven adult ruminally fistulated rams (2 years old; 74 ± 2.5 kg body weight) were randomly allocated to seven experimental diets in a changeover design. Treatments were as follows: whole FB without LB (WFB − LB); whole FB with LB (WFB + LB); FB tops without LB (FBT − LB); FB tops with LB (FBT + LB); FB bulbs without LB (FBR − LB); FB bulbs with LB (FBR + LB) and corn silage (CS) as control. Results LB inoculation did not affect silage chemical composition. FB bulb silage had lower pH than FB top silage. Dry matter intake (DMI) was highest for WFB + LB and lowest for FBT − LB ( p < 0.001). Dry matter (DM) and organic matter (OM) digestibility were highest for CS and lowest for FBT − LB ( p < 0.001). Ruminal pH and NH 3 ‐N concentration were highest in sheep fed whole FB silage ( p < 0.001). The acetate:propionate ratio was highest in FBT + LB and FBT − LB, followed by whole FB silage. FBT + LB and FBT − LB showed higher pH and NH 3 ‐N but lower lactic acid concentration and flieg point value than other treatments. Conclusion Silage made from whole FB (with or without LB) could be a promising alternative to CS for sheep, based on digestibility and rumen function parameters.